A Case Study Of Culture On Global Marketing Strategies Among Asian Countries - Mosaheb, Muhammad Yaaseen Djameel (2009)
This research based on both qualitative and quantitative research, companies are expected to get a broader idea of how to tackle the culture difference and minimize its effects on their global marketing strategies.